Excess weight and thinness over two decades (1996–2015) and spatial distribution in children from Jujuy, Argentina - Bustamante, María José (2021)
Background: The increase of excess weight around the world is progressive and sustained in children. This is the most prevalent form of malnutrition in this population and they represent the major public health problem in developed and developing countries. The aim of this study was to analyze the magnitude of change in thinness and excess weight prevalence in 4–7 years-old schoolchildren from Jujuy (Argentina), between 1996 and 2015 and to examine the association according to sex and school location. Methods: Cross-sectional study. Data was obtained from databases of School Health programs and it is representative of the city school population. For the analysis, 31,014 schoolchildren between 4 and 7 years old were evaluated, 20,224 from the first period (1996–2001) and 10,790 from the second (2010–2015). The city was partitioned in three different areas determined by the rivers that cross it. Nutritional status was determined by BMI for age with the criteria suggested by the International Obesity Task Force. The percentage of malnutrition change between periods was calculated and a binomial regression model was adjusted. Results: Between periods, a significant (p-value< 0.0001) increase in the prevalence of overweight from 15.1% (CI 14.6–15.6%) to 18.1% (CI 17.4–18.8%) and obesity from 5% (CI 4.7–5.3) to 10.7% (CI 10.1–11.3%), and a decrease of thinness prevalence from 6.3% (CI 6.0–6.7%) to 4.7% (CI 4.3–5.1%) were observed. The percentage of change in the prevalence of obesity was very high in all areas and in both sexes (103.5% girls; 125.6% in boys), being higher in the south for girls (122.4%) and in the north for boys (158.8%). Besides, being a boy was inversely associated with the presence of excess weight and, as the age increases, the presence of obesity does it too. By analyzing the effect of the school location, the south and north zones had an inverse association with the presence of obesity. The period has a direct association with the presence of excess weight. Conclusion: The study contributes with valuable information on the magnitude of the increase in obesity in schoolchildren and suggests a possible correlation with sex and spatial distribution in the capital city of Jujuy.